A Survey on Internet of Things - Bairagi, V.K; Joshi, S.L; Barshikar, SH (International Journal of Computer Sciences and Engineering, 2018)
Internet has made a significant impact on our economy and society. With the advances in information and communication technologies, Internet of Things (IoT) has emerged as one of the most powerful communication paradigms of the 21st century representing the trend of future networking and is leading the wave of the IT industry revolution. Advancement in technology related to data collection, such as embedded devices and RIFD technology had led to increase in number of devices that are connected to the net and transmit the data continuously. The continuation of this trend is poised to evolve as an “Internet of Things” where the web will provide a medium for objects to become interactive. IoT makes internet more pervasive by extending the concept of internet to accommodate each and every object existing in this world or likely to exist in the coming future. These objects continuously generate information about the physical world, communicate with other objects and the seamless interactions among them lead to many different applications such as home automation, smart grid, smart city, traffic management, etc. This paper addresses different perspectives, challenges, applications and current world wide activities related to IoT.